The education and training of seven African American U.S. Army officers for World War I and its aftermath - Harris, Bernard F. Jr. (Kansas State University, 2022)
This historical research study examines how seven African Americans used their civilian education and military training to prepare themselves for combat, execute combat operations in France, and later make lasting contributions to American society. The knowledge constructed in this study derives from an exhaustive review of primary and secondary source material from archives, museums, and libraries around the United States and France. The study examines the legal foundation of the segregationist system the seven endured and compares the civilian higher education institutions they attended before their military careers. The study adds to existing scholarship in the depth of detail provided in examining their military training at Fort Des Moines, Iowa, and other locations in the United States, and France during the war. The study argues that civilian education was not enough in America for African American men referenced as Black American men in the study to overcome the status quo of White hegemony in a segregated society. These men needed the opportunity to scaffold their civilian education onto military training to become successful military and later civilian leaders, earning enough social capital to personify W. E. B. Du Bois’s touted Talented Tenth concept. The study also provides an aggregated comparison of similar experiences of other nationalities to underscore the relevance of the information presented. The need for this study became apparent after the 100th commemoration of the end of World War I exposed the limited information available on the topic.
Keywords: Education; Segregation; African American; Constructivism; Military; Training